Tislelizumab immunotherapy combined with chemotherapy in the treatment of a patient with primary anterior mediastinal undifferentiated pleomorphic sarcoma with high PD-L1 expression: A case report and literature review - Yang, Hujuan; Qin, Zhiquan; He, Xianglei; Xue, Qian; Zhou, Hongying; Sun, Jie; Li, Xiaoyi; Zhao, Tongwei (Frontiers in Oncology, 2023)
Undifferentiated pleomorphic sarcoma (UPS) is a rare and aggressive soft tissue tumor with a high degree of malignancy and rapid progression. It usually occurs in the extremities, retroperitoneum, and abdomen, whereas it rarely arises in the mediastinum. The main treatment is surgical resection. The prognosis of patients with advanced sarcoma is poor. Doxorubicin monotherapy is the standard first-line chemotherapy for most advanced soft tissue sarcomas (STS), but the prognosis is generally unsatisfactory. Immune checkpoint inhibitors (ICIs) have been established as therapies for many solid cancers in recent years; however, evidence on the efficacy of ICIs in undifferentiated sarcoma is scarce, mostly consisting of small studies, and no ICIs are currently approved for use in sarcomas. We report the case of a middle-aged man with primary mediastinal UPS (PD-L1 tumor proportion score = 80%), who was treated with sequential tislelizumab monotherapy maintenance after six cycles of tislelizumab combined with epirubicin, efficacy evaluation was partial remission (PR), progression-free survival (PFS) was 8.5 months, and grade 1 fatigue was identified as an adverse event.